Examining the Association Between AI-Supported Cognitive Scaffolding and Conceptual Understanding in Secondary Science Learning - Anggi Widiarni; Yuli Yanti (AI and Developmental Insights in Education, 2026)
Artificial intelligence (AI) is increasingly used to support adaptive feedback, prompts, and learning analytics in science education, yet the mechanisms linking AI-supported scaffolding to conceptual understanding remain underexplored. This study examined whether metacognitive awareness mediated the association between AI-supported cognitive scaffolding and conceptual understanding, and whether prior knowledge moderated the scaffolding–metacognition pathway. A quasi-experimental pretest–posttest control-group design was conducted with 214 Grade 9–10 students from four intact science classes in Bandar Lampung, Indonesia. Students were assigned to either an AI-scaffolding condition (n = 108) or a conventional instruction condition (n = 106) over a 12-week intervention. Conceptual understanding was assessed using a 40-item curriculum-aligned test (α = .87), while metacognitive awareness was measured using a 30-item adapted inventory (α = .82). Results showed that students in the AI-scaffolding condition achievedhigher post-test scores and greater learning gains. Metacognitive awareness partially mediated this association, and the indirect effect was stronger among students with lower prior knowledge.